2017
DOI: 10.1590/1807-1929/agriambi.v21n1p32-37
|View full text |Cite
|
Sign up to set email alerts
|

Leaf gas exchange in cowpea and CO2 efflux in soil irrigated with saline water

Abstract: A B S T R A C TLeaf gas exchanges in plants and soil respiration are important tools for assessing the effects of salinity on the soil-plant system. An experiment was conducted with cowpea irrigated with saline water (0, 2.5, 5.0, 7.5, 10.0 and 12.5 dS m -1 ) prepared with two sources: NaCl and a mixture of Ca, Mg, Na, K and Cl ions in a randomized block design and a 6 x 2 factorial scheme, with four replicates, totaling 48 experimental plots. At 20 days after planting (DAP), plants were evaluated for net phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
1
13
0
3
Order By: Relevance
“…These reductions of internal CO 2 concentration with increase in salinity levels observed in soursop cv. 'Morada Nova' are a common response of plants to salt stress, which occurs probably due to the lower CO 2 diffusion in the substomatal chamber due to stomatal closure (Oliveira et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…These reductions of internal CO 2 concentration with increase in salinity levels observed in soursop cv. 'Morada Nova' are a common response of plants to salt stress, which occurs probably due to the lower CO 2 diffusion in the substomatal chamber due to stomatal closure (Oliveira et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to Silva, Ribeiro, Ferreira-Silva, Viégas and Silveira (2011a), the reduction in CEi is associated with decreased RuBisCO activity. Oliveira, Souza, Cunha, Silva and Veloso (2017), in an experiment with cowpea irrigated using water with six levels of electrical conductivity (0, 2.5, 5.0, 7.5, 10.0, and 12.5 dS m -1 ), also reported that there was a linear decrease in CEi as a function of the increase in ECw levels.…”
Section: Resultsmentioning
confidence: 90%
“…As a consequence of the reduction of leaf water potential with saline irrigation, stomatal closure occurred, thus reflecting a low CO 2 assimilation rate [42,48,49]. Nevertheless, an improvement of WUE i was noted under salinity conditions as an adaptation of moderately salinity tolerant plants [50]. The greater amount of leaf K accumulated in these plants than in those irrigated with control water would also help to prevent a greater reduction in water relations by regulating cellular osmotic potentials and thus, stomatal closure [51].…”
Section: Discussionmentioning
confidence: 99%